MOBILE-LEARNING FEEDBACK AND STUDENTS’ SELF- EFFICACY IN NEW NORMAL POST COVID-19 - Nurul Hidayah (Kopertis Region IV Jabar and Banten, 2020)
Nowadays, we live in a digital age and New Normal of COVID-19. There is a massive migration of face-to-face teaching learning method to online or mobil- teaching and learning. It is required to do a physical distancing among school members to stop the spreading of the COVID-19. Mobile-learning is a must to keep education process continue while we remain to stay at home. The successful of mobile teaching and learning process depends on several aspects, one of them is students’ self-efficacy. Students’ self-efficacy determines how hard students try to accomplish the task given and to the extent students commit taking part in the mobile learning process during this pandemic COVID-19. It also determines to what extent students want to challenge themselves. To sum up, self-efficacy plays a crucial role in students’ achievement using mobile-learning method during this pandemic era. There is a significant relationship between feedback and self-efficacy. Therefore, educationalist is suggested to provide mobile-learning feedback to enhance students’ self-efficacy to keep the students commit to taking part in the teaching-learning process. An elaborated feedback affected students’ self-efficacy more although it is only a video feedback.